Modelling spatial patterns of wildfire occurrence in South-Eastern Australia. Issue 6 (1st November 2016) - Zhang, Yang; Lim, Samsung; Sharples, Jason John
ABSTRACT: This paper describes the development and validation of spatial models for wildfire occurrence at a broad landscape scale. The hotspots databases from the Moderate Resolution Imaging Spectroradiometer (MODIS) and logistic regression models are investigated for the comprehensive understanding of environmental and socioeconomic determinants regulating the spatial distribution of wildfires over the 11-year period 2003–2013. The probability of occurrence of at least one fire on a 1 km 2 grid cell in a 1, 030, 000 km 2 region located in South-Eastern Australia is studied for the prediction of future fire occurrence. Our research shows that wildfires are most likely to occur in mountainous areas, forests, savannas and lands with high vegetation coverage, and are less likely to occur on grasslands and shrublands. Wildfires also tend to occur in areas near human infrastructures. Environmental variables are strong individual predictors of fire occurrence while socioeconomic variables contribute more to the final model. The influence of environmental and socioeconomic conditions on wildfire occurrence and the spatial patterns of wildfires identified in this study can assist fire managers in implementing appropriate management actions in South-Eastern Australia. This paper also demonstrates the potential of applying the MODIS active fire product in wildfire occurrence studies.